Framework para transferência de unidades hospitalares: gerenciamento de projetos em um hospital universitário - Alcantara, Amanda Falcão (2021)
This research aims to develop and apply a framework with the use of project management management in an issue related to organizational change / change within a health institution. In addition to identifying relevant authors, articles and journals on the topic studied in the literature. For this, bibliometric analysis is used to collect these data and the use of action research for the development and application of the method. The chosen institution was a university hospital in the process of transferring hospital units to a new hospital structure, a problem to be resolved is how to carry out a transfer without stopping the operation and guaranteeing the safe transfer of equipment and patients, in addition to committed employees. To carry out the transfer, it was necessary to carry out the planning, management, coordination and control of activities, in addition to the knowledge management of the parties involved. Given this scenario, the research question is the creation of a framework and its application in a hospital environment through project management options, which are traditional and agile, to observe the intervention of approaches in the results obtained in their intervention. It can be noted that in carrying out the planning, the use of agile approaches was essential, as it is unprecedented for all completed parts, the transfer of hospital units, establishing a scenario of uncertainties and instabilities, with constant need for scope changes during planning. In order to associate two distinct approaches to project management, a traditional approach starts from the final product of the planning, that is, no execution process, based on planning, but due to a worldwide pandemic caused by the new coronavirus there were several changes in the execution of the plan, however the planning helped in risk management and strengthening of communication with those affected and especially in contracting the outsourced company to carry out the transfer.